Isolation and identification of culturable halophilic bacteria with producing hydrolytic enzyme from Incheh Broun hypersaline wetland in Iran - Zarparvar, P.; Amoozegar, M. A.; Babavalian, H.; Reza Fallahian, M.; Tebyanian, H.; Shakeri, F. (Cellular and Molecular Biology, 2016)
Incheh Broun hypersaline wetland is located near the border of Turkmenistan in thenorth of Iran. This wetland is notable because of salinity (280g/l) and alteration in pH range (2.8 to 6.8). Eastern part of wetland is affected by wastewater of iodine extraction factory. Samples were taken from soil, water and salt. Totally, 400 bacterial strains were isolated of which 194 strains were Gram-positive bacilli, 184 strains were Gram-negative rod and 22 strains were Gram-positive cocci. According to phylogenetic analysis of 16S rRNA, selected strains were placed in three taxonomic phyla including Firmicutes, Actinobacteria and Gammaproteobacteria. Optimum growth was evaluated for salt and 22 strains were found to be moderate halophile and 33 strains were halotolerant. Production of lipase, amylase, gelatinase and protease was examined. Gram-positive bacilli were the main producers of hydrolytic enzymes. Gelatinase and protease were the most frequent enzymes. Gram–positive cocci were the main producers of lipase but they didn’t produce amylase.